Examining the availability/findability of stimuli employed in social media and body image research - David Smailes; Arnela Aleksandra; Megan Coakley; Susan Mair; Joe Ventress (PLoS ONE, 2025)
Concerns over the trustworthiness of the research findings generated in Psychology (as well as other disciplines) has led to calls for the adoption of practices that make research more open, transparent, and reproducible. One of these practices is the open sharing of research materials, such as task stimuli. There is some evidence that, generally, the uptake of this practice has been slow in Psychology. The aim of this study was to examine the availability/findability of the stimuli used in a sample of papers that investigated the effect of exposure to images from social media on participants’ body image, as this may be a field where progress in the open sharing of task stimuli may be especially slow. We coded the method sections of 38 studies (published across 36 articles from 2012 to 2021) in terms of the availability/findability of the images they employed and found that in only two articles were we able to fully access task stimuli. We also found no evidence that the sharing of images used as task stimuli had increased over time. We discuss likely reasons for this reticence to share task stimuli in this field, the impact this has on reproducibility, replicability, and research waste, and ways in which this issue can be addressed. All study materials and data are available at doi.org/10.17605/osf.io/wpvst.